Music Lessons for the Study of Affect - McCrae, Robert R. (Frontiers in Psychology, 2021)
Some accounts of the evolution of music suggest that it emerged from emotionally expressive vocalizations and serves as a necessary counterweight to the cognitive elaboration of language. Thus, emotional expression appears to be intrinsic to the creation and perception of music, and music ought to serve as a model for affect itself. Because music exists as patterns of changes in sound over time, affect should also be seen in patterns of changing feelings. Psychologists have given relatively little attention to these patterns. Results from statistical approaches to the analysis of affect dynamics have so far been modest. Two of the most significant treatments of temporal patterns in affect—sentics (Clynes, 1977) and vitality affects (Stern, 1985)—have remained outside mainstream emotion research. Analysis of musical structure suggests three phenomena relevant to the temporal form of emotion: affect contours, volitional affects, and affect transitions. I discuss some implications for research on affect and for exploring the evolutionary origins of music and emotions.